Poor health literacy associated with stronger perceived barriers to breast cancer screening and overestimated breast cancer risk - Poon, Paul K. M. (2023)
Low health literacy (HL) is negatively associated with mammography screening uptake. However, evidence of the links between poor HL and low mammography screening participation is scarce.